Business clip art (Rugeley : Focus Multimedia Limited, 2002)
Contains 300 scalable clip art images, printable in either full-color or black and white, in CGM, WMF, EPS, CPC, and PCX formats.
Ελάχιστες απαιτήσεις συστήματος: IBM PC or compatible; Windows 3.1, Windows 3.11, or Windows 95 or better; CD-ROM drive.
Keywords: CD-ROMs.; Clip art -- CD-ROMs.; Business -- Computer graphics -- CD-ROMs.